Bursting photosynthesis: designing ad-hoc fluorophores to complement the light harvesting capability of the photosynthetic reaction center. Issue 1689 (26th June 2014) - Ragni, Roberta; Omar, Omar Hassan; Tangorra, Rocco Roberto; Milano, Francesco; Vona, Danilo; Operamolla, Alessandra; La Gatta, Simona; Agostiano, Angela; Trotta, Massimo; Farinola, Gianluca M.
ABSTRACT: The covalent functionalization of photosynthetic proteins with properly tailored organic molecular antennas represents a powerful approach to build a new generation of hybrid systems capable of exploiting solar energy. In this paper the strategy for the synthesis of the tailored aryleneethynylene organic fluorophore (AE) properly designed to act as light harvesting antenna is presented along with its successful bioconjugation to the photosynthetic reaction center RC from the bacterium Rhodobacter sphaeroides .